Strategi Mengatasi Stres Dan Mempertahankan Kesejahteraan Keluarga Pada Orang Tua Tunggal: Studi Kasus Pamulang Barat - Prayoga Pangestu; Amin Tohari (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Single parents face stressful challenges that detrimentally affect individual well-being and disrupt family dynamics. This research reveals various strategies for coping with stress, including emphasizing solutions, maintaining emotional balance, and seeking social support. Through a qualitative approach, interviews with six single parents uncovered diverse strategies, such as emphasizing solutions, maintaining emotional balance, engaging in positive activities, participating in spiritual practices, and relying on a strong community role. Their perseverance in meeting family needs, providing quality education, and maintaining well-being demonstrates inspirational determination. The research highlights the crucial role of social support and perseverance in responding to the impact of stress on single parents, influencing overall family well-being.